Gross Alpha and gross beta radioactivity and heavy metal concentration profiles of well water of the Calahunan Dump site, Mandurriao, Iloilo City - Amarante, Hena Charma; Basquez, Mark Anthony; Brunio, Christian Allan
This study aimed to establish presence of radioactivity and concentration of heavy metals specifically lead and chromium in drinking water from wells within one-kilometer radius from the approximated center of of the Calahunan dump site.